2018
DOI: 10.2147/ott.s168275
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of weekly nab-paclitaxel plus cisplatin with concurrent intensity-modulated radiotherapy in patients with inoperable, locally advanced esophageal cancer: a pilot trial

Abstract: BackgroundNab-paclitaxel is produced by the combination of paclitaxel particles with human serum albumin. Encouraging efficacy has been observed with nab-paclitaxel-based chemotherapy in a variety of solid tumors. The aim of the study reported here was to evaluate the efficacy and safety of weekly nab-paclitaxel plus cisplatin with concurrent intensity-modulated radiotherapy in patients with locally advanced esophageal cancer.MethodsSeventeen patients with esophageal cancer were enrolled between July 2014 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
3
10
0
Order By: Relevance
“…The median PFS of the single-agent group was 20 months, whereas that of the double-agent group was 21 months. These OS and PFS rates were consistent with those previously reported [27,28]. We found no significant difference between the single-agent group and the double-agent group in this study, indicating the need for a phase III trial to further determine the long-term effect of single-and doubleagent concurrent chemoradiotherapy.…”
Section: Adverse Events: Controlsupporting
confidence: 92%
See 1 more Smart Citation
“…The median PFS of the single-agent group was 20 months, whereas that of the double-agent group was 21 months. These OS and PFS rates were consistent with those previously reported [27,28]. We found no significant difference between the single-agent group and the double-agent group in this study, indicating the need for a phase III trial to further determine the long-term effect of single-and doubleagent concurrent chemoradiotherapy.…”
Section: Adverse Events: Controlsupporting
confidence: 92%
“…This could be because cisplatin does not aggravate esophageal and pulmonary injury, and there was no significant difference in the radiotherapy dose between the two groups. The overall incidence rate of hematotoxicity in this trial is relatively similar to that of previous studies [27][28][29][30][31], but that in the single-agent group is higher [24]. This is attributed to the long-term oral administration of S1 (from Monday to Friday for six consecutive weeks), which may have aggravated the toxicity.…”
Section: Study Completedsupporting
confidence: 83%
“…Target volumes were as described previously (Methods in Supplement 2). 19 Patients received cervical, thoracic, and upper-abdomen CT scans and upper gastrointestinal radiography at baseline, every 8 weeks during treatment, and every 12 weeks after treatment until disease progression. All patients underwent endoscopic ultrasonography, the standard clinical practice for potential tumor biopsy, at baseline and after 40 Gy radiation 20 (ie, at the end of 4 weeks of radiotherapy) in order to confirm pathological response rates and perform exploration tests.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al [ 13 ] demonstrated that weekly nab-paclitaxel plus cisplatin with concurrent definitive radiotherapy is an effective and well-tolerated treatment option for ESCC. In addition, Wang et al [ 14 ] compared the values of nanoparticle albumin-bound paclitaxel plus cisplatin (nab-TP) vs solvent-based paclitaxel plus cisplatin (sb-TP) and found that nab-TP demonstrated a higher ORR (50% vs 30%, P = 0.082) and disease control rate (81% vs 65%, P = 0.124) than sb-TP, as well as a longer median PFS (6.1 mo, 95%CI: 5.3-6.9) ( P = 0.029).…”
Section: Discussionmentioning
confidence: 99%